The Effect of Parenting Patterns and Digital Literacy on Social-Emotional Development in Early Children - Supriyadi, Supriyadi; Maesyaroh, Siti (Jurnal Ilmiah Profesi Pendidikan, 2023)
Early childhood education is tasked with providing efforts to guide, stimulate, hone, and provide activities that will produce children with their abilities and skills. This study aims to reveal the effect of parenting and digital literacy on the social-emotional development of early childhood. The research methodology used is quantitative research with a survey approach. The population of this study was all group B students in Cluster 8 Pondok Cabe Ilir Village, totaling 285 students. The research sample is 205. The sampling technique uses random sampling. The research data were obtained from valid and reliable instruments. The results of the study 1) Parenting has a positive effect on the Social Emotional Development of Early Childhood; 2) Digital Literacy has a positive effect on Early Childhood Social Emotional Development; 3) Parenting and Digital Literacy simultaneously or simultaneously have a positive effect on Early Childhood Social Emotional Development; 4) The Variables of Early Childhood Social Emotional Development (Y) can be explained by Parenting Patterns (X1) and Digital Literacy (X2), so it can be concluded that the influence of Parenting Patterns and Digital Literacy together on Early Childhood Social Emotional Development by 60.4%.